1985
DOI: 10.1159/000173960
|View full text |Cite
|
Sign up to set email alerts
|

<sup>131</sup>I-MIBG - A New Agent in Diagnosis and Treatment of Pheochromocytoma

Abstract: The newly developed radiopharmaceutical, 131I-metaiodobenzylguanidine (131I-MIBG), has been shown to be efficacious for the location of intra- and extra-adrenal, primary pheochromocytomas and metastatic, malignant pheochromocytomas (11.4% false-negative and 1.8% false-positive in patients with proven pheochromocytomas). Preliminary experience in selected patients with malignant pheochromocytoma suggest that therapy using large doses of I31I-MIBG results in partial tumor regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
2
15
0
1
Order By: Relevance
“…Heart failure [13,21], cardiomyopathy [14--20], myocardial infarction [2,[8][9][10][11] and diabetic autonomic neuropathy [2,7,13] can all injure the sympathetic nervous system leading to functional or scar-associated denervation. Transient myocardial ischaemia produces regional sympathetic denervation [22], PET studies [12] have demonstrated the sensitivity of the myocardial sympathetic nervous system to ischaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart failure [13,21], cardiomyopathy [14--20], myocardial infarction [2,[8][9][10][11] and diabetic autonomic neuropathy [2,7,13] can all injure the sympathetic nervous system leading to functional or scar-associated denervation. Transient myocardial ischaemia produces regional sympathetic denervation [22], PET studies [12] have demonstrated the sensitivity of the myocardial sympathetic nervous system to ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Infarction leads to sympathetic denervation in the infarcted myocardium and also in a broad area apical and lateral to the zone of the scar [2,[8][9][10][11] with a potential for arrhythmogenicity [9,12]. Other studies performed in patients with heart failure [13], hypertrophic and dilated cardiomyopathies [14][15][16][17][18][19][20], or diabetic autonomic neuropathy [2,13] have shown reduced MIBG uptake and enhanced MIBG washout indicating neuronal dysfunction. Examination of transplanted hearts has revealed nearly undetectable neuronal and non-neuronal uptake [21] indicative of complete denervation.…”
Section: Introductionmentioning
confidence: 99%
“…(9) in cases untreatable by other techniques, in cases expected to survive at least one year without therapy, and in cases whose tumor uptake of 131I-MIBG would be sufficient to give at least 20 rads/mCi (0.54 Gy/MBq) in a lesion. Although multiple bone metastases had been reported resistant to 131I-MIBGtherapy (4), our patient responded to the first treatment with the disappearance or reduction in size of the metastatic tumor, which was associated with The drug has been widely used in Europe and the U.S.…”
Section: Case Reportmentioning
confidence: 99%
“…
A 47-year-old man had surgery for paraaortic paraganglioma in 1980and 1985. In 1987, his urinary excretion of catecholamines and metabolites was extremely high.
…”
mentioning
confidence: 99%
“…Since 131 I-MIBG was reported to visualize tumors of the adrenal medulla in the early 1980s [3,4], 131 I-MIBG and 123 I-MIBG have been widely used for detecting lesions in patients with malignant neuroendocrine tumors, such as malignant pheochromocytomas, malignant paragangliomas, medullary thyroid carcinomas, carcinoid tumors and neuroblastomas [5][6][7][8][9]. 123 I-MIBG has superiority over 131 I-MIBG with diagnostic use, because the γ-ray energy of 123 I (159keV) befits the image quality and lesion detectability for scintigraphy compared with that of 131 I (364keV) [10][11][12].…”
Section: Introductionmentioning
confidence: 99%